Analysis of Human Error Factors in Traffic Accident (Case Study: Tangerang-Merak Toll Road) - Dika Ruslaninur Yadi; Martha Leni Siregar; Sutanto Soehodho (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2026)
Traffic accidents carry significant social, economic, and public safety consequences. In Indonesia, human error accounts for over 60% of accident cases, based on data from the Indonesian National Police Traffic Corps. The Tangerang-Merak Toll Road, a vital corridor connecting industrial areas and major ports in western Java, has seen a notable increase in accidents in recent years, underscoring the need for a deeper understanding of human error contributions. This study aims to analyze the influence of human error-related factors, including driving behavior, risk perception, environmental factors, and individual characteristics, on traffic accidents on the Tangerang-Merak Toll Road. A quantitative approach using Structural Equation Modeling Partial Least Squares (SEM-PLS) was employed to examine these relationships. Data were collected through observation, literature review, and questionnaires. The model demonstrates strong explanatory power, with an R-square value of 0.606, indicating that 60.6% of the variation in traffic accidents is explained by the included variables. Driving behavior is the most dominant factor, with a path coefficient of 0.669, followed by risk perception (0.248). Environmental factors show a negative relationship (-0.478), suggesting that certain environmental conditions may reduce accident risk. Individual characteristics exhibit smaller and mixed effects, including driving experience (0.134), frequency of toll road usage (-0.149), vehicle type (-0.073), and gender (-0.144).